Youth and political participation: a view over the Participatory. - Quadros, C.; Quadros, I. (Revista Latina de Comunicación Social, 2015)
The "Youth Participatory Observatory" is a social network released in July 2013 by the Brazilian government to encourage the collaboration of the youth over discussions addressed to youth policies. This interactive environment renders an integrated work with digital social networks for the purpose to get to know the youth and its concerns. The proposition is to enable debate to furnish subsidies towards public policies, legislation and other important subjects for the Brazilian youth. The essay document of Youth Participatory Observatory highlights that young people have long been askingfor a reliable space to discuss with researchers, managers and all the youngsters over the focal point of interest. Upon this article, we describe the creation process of the Participatory and furnish the analysis by means of the created groups as per the focal interest of the attending youngsters.